HUBUNGAN DUKUNGAN KELUARGA DENGAN KEPATUHAN BEROBAT PADA PENDERITA HIPERTENSI DI WILAYAH KERJA PUSKESMAS CIAMIS TAHUN 2019 - Riyanto Agung Pamungkas; Siti Rohimah; Dini Nurbaeti Zen (Universitas Galuh Ciamis, 2020)
Compliance with hypertension treatment is the main aspect in treating hypertension. One of the factors that can influence medication adherence is family support. The purpose of this study was to determine the relationship between family support and adherence to treatment in patients with hypertension in the work area of Ciamis Health Center.The design of this study uses correlational design. The population in this study were patients with hypertension in the work area of Ciamis Health Center, which were 13,273 people and the study sample used purposive sampling so that the samples obtained were 99 people. Data collection techniques used were questionnaires and observations. The results showed a relationship between family support and adherence to treatment in hypertensive patients in the Ciamis Community Health Center work area. Based on the results of the Kendal-Tau analysis with a 95% confidence level and a 5% error level, the correlation coefficient value of family support with treatment compliance is equal to r = 0.526 with a significance level of p value of 0.049 < α 0.05. That is, the higher the family support given to hypertension sufferers, the higher the compliance.Suggestions for further researchers are expected to conduct further research on the importance of family support to further improve adherence to treatment in patients with hypertension, because in this study most of the family support provided moderate support. Or examine other factors that can improve the compliance of hypertensive patients in treatment. Keywords: Family Support, Compliance with Hypertension TreatmentReferences: 31 (2002-2018)